"Eating the Stones of the Earth": Romancing the Scientific Production of Food in Technological Utopias - Botelho, Teresa (Cadernos de Literatura Comparada, 2017)
In many examples of contemporary speculative fiction, the projection of possible futures, shaped by concerns over the preservation of the ecosystem and the integrity of species, uses the cultural tropes of food production and consumption as symbolic tools to represent loss or threat to what seems the order of the natural world. Conventional and natural food is often invested as an anchor of familiarity in imagined changed worlds, frequently functioning as a signifier of nostalgic resistance against the new social and cultural order, while new artificial foodstuffs perform the function of accentuating the pre-apocalyptic or post-apocalyptic collapse of the natural and the pastoral. This rejection of the intrusion of high technology in food production contrasts with the dream of sterile scientific food production detached from agricultural practices that emerges in several nineteenth- and early twentieth-century American utopias. This paper discusses two of these texts, Mizora, by Mary Bradley Lane (1898), the first literary imagining of a women-exclusive non-patriarchal society, and Roadtown, by Edgar Chambless (1910), and examines how they project strategically opposite dreams of the relation between the agricultural and the laboratorial, the natural and the technological, as represented by the protocols of food production and consumption.